2013
DOI: 10.3233/cbm-140392
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A is elevated in sera of patients with poorly differentiated ovarian papillary serous cystadenocarcinoma

Abstract: Elevation of IL-17A in a high percentage of ovarian serous cystadenocarcinoma and lack of this cytokine in healthy individuals makes it a specific candidate in diagnosis, follow up or immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To our best of knowledge, there is no report on the serum IL-17A levels in Fars province of Iran with a relatively high rate of gastric cancer. In the previous studies in this same area, we have observed a higher level of IL-17A in the sera of patients with colorectal (Nemati et al, 2015) as well as glioma, bladder and ovarian cancers (Doroudchi et al, 2013a;Doroudchi et al, 2013b;Malekzadeh et al, 2013). Therefore, in a preliminary study to evaluate the possible increase of IL-17A in the sera of GC patients in our area, we measured the IL-17A and its association with some clinicopathological factors in a group of Iranian patients with gastric cancer residing in Fars region.…”
Section: Il-17a Levels In the Sera Of Patients With Gastric Cancer Show Limited Elevationmentioning
confidence: 64%
“…To our best of knowledge, there is no report on the serum IL-17A levels in Fars province of Iran with a relatively high rate of gastric cancer. In the previous studies in this same area, we have observed a higher level of IL-17A in the sera of patients with colorectal (Nemati et al, 2015) as well as glioma, bladder and ovarian cancers (Doroudchi et al, 2013a;Doroudchi et al, 2013b;Malekzadeh et al, 2013). Therefore, in a preliminary study to evaluate the possible increase of IL-17A in the sera of GC patients in our area, we measured the IL-17A and its association with some clinicopathological factors in a group of Iranian patients with gastric cancer residing in Fars region.…”
Section: Il-17a Levels In the Sera Of Patients With Gastric Cancer Show Limited Elevationmentioning
confidence: 64%
“…ey also observed a higher concentration of the assessed cytokine in the serum of patients with OC with a low degree of histological differentiation, compared to cancer with a high and medium degree of differentiation. According to them, this observation may suggest the existence of various sources of IL-17 ( 17 or cancer cells) involved in the production of this cytokine at particular stages of tumor progression [52]. Tang et al showed a higher level of IL-17 expression in the tissue of ovarian malignant tumors, compared to benign tumor tissue and controls.…”
Section: Controlmentioning
confidence: 99%